Peter Holland, homeobox genes, and the developmental basis of animal diversity - Shimeld, S (2008)
In 1867 Alexander Kowalevsky published an account of the development of the cephalochordate Amphioxus lanceolatus (now known as Branchiostoma lanceolatum) (Kowalevsky, 1867). Together with his study of the development of urochordates (Kowalevsky, 1866; 1871), this introduced a new way of thinking about the relationship between the evolution and development of animals, and established the basis for long-standing theories of the evolutionary origin of vertebrates. Some one hundred and fifty years later, cephalochordates and urochordates are again in the spotlight, as molecular biology and genome sequencing promise further revelations about the origin of vertebrates. The work of the 2006 Kowalevsky Medal winner, Peter Holland (Fig. 1), has played a central role in their reinstatement (see Mikhailov and Gilbert (2002) for more details of the history of the Kowalevsky Medal). Here, I profile Peter Holland's contribution to the rebirth of Evolutionary Developmental Biology in general and the study of homeobox genes and vertebrate origins in particular. © 2008 MAIK Nauka.